IMPLEMENTASI TRACER STUDY BERBASIS WEB ROBOT TELEGRAM DI SMKN IHYA ULUMUDDDIN BANYUWANGI - Prasetyo, Junaedi Adi; Ayatullah, Mohamad Dimyati; Wibowo, Galih Hendra; Suardinata, I Wayan (UNIVERSITAS PGRI MADIUN, 2022)
Abstract. Alumni tracking or what is known as a tracer study is one of the most important activities at this time, especially in vocational-based education. With the link and match carried out in schools with industry, schools will be able to know the quality of their graduates and further information can be used to improve the learning curriculum.Currently, Ihya Ulumuddin Vocational School is conducting a tracer study still using the manual method with paper, when their alumni come to school and the results are not optimal. Completing a study tracker with this method is only able to track less than 15% of the number of graduates each year so that the picture of graduates of SMK Ihya Ulumuddin is very lacking. This data tracking study must also be submitted to the Director General of Vocational Schools at the end of each year and the school always has difficulties in providing this data. From this problem, it is said that the creation of a telegram robot application that is connected to the tracer study web application is the solution to the implementation of this tracer study. The creation of this system begins after building the system with the SMK and the application is complete, trials and implementations are carried out after the alumni graduate. Workshops and training on tracer studies were also carried out to support the implementation of this Telegram-based tracer study system. From the results of this community service, a total of 74% of the graduates were obtained in 2021. With the telegram robot that has been implemented, the tracer study implementation will assist in answering tracer study questions, making it easier to collect data on alumni of SMK Ihya Ulumuddin in an effective and efficient manner in every year. Abstrak. Pelacakan alumni atau yang disebut tracer study merupakan salah satu kegiatan yang penting dilakukan saat ini, khususnya pada pendidikan berbasis vokasi. Dengan adanya link and match yang dilakukan sekolah dengan industri, maka sekolah akan dapat mengetahui kualitas lulusannya dan nantinya informasi ini dapat digunakan untuk memperbaiki kurikulum pembelajaran. Saat ini, SMK Ihya Ulumuddin melakukan tracer study masih menggunakan cara manual dengan kertas, ketika alumni mereka datang ke sekolah dan hasilnya kurang optimal. Pengisian tracer study dengan metode ini hanya mampu melacak kurang dari 15% jumlah lulusan setiap tahunnya sehingga gambaran mengenai lulusan SMK Ihya Ulumuddin masih sangat kurang. Data tracer study ini juga wajib disampaikan kepada Dirjen Vokasi setiap akhir tahun dan pihak sekolah selalu mengalami kesulitan dalam menyediakan data ini.. Dari masalah tersebut disimpulkan bahwa pembuatan sebuah aplikasi robot telegram yang terhubung dengan web aplikasi tracer study adalah solusi dari pelaksanaan tracer study ini. Pembuatan sistem ini dimulai dengan berdiskusi dalam membangun sistem Bersama pihak SMK dan setelah aplikasi selesai, ujicoba dan implementasi dilakukan setelah alumni lulus. Pelaksanaan workshop dan pelatihan mengenai tracer study juga dilaksanakan dalam mendukung implementasi sistem tracer study berbasis tekegram ini. Dari hasil pengabdian masyarakat ini, didapatkan pengisan sejumlah 74% dari jumlah lulusan di 2021. Dengan adanya robot telegram yang sudah diimplementasikan ini, pelaksanaan tracer study akan terbantu dalam menjawab pertanyaan tracer study sehingga mempermudah pengelola dalam mengumpulkan data alumni SMK Ihya Ulumuddin secara efektif dan efisien dalam setiap tahun.